2015
DOI: 10.1016/j.ijrobp.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Lung Texture in Serial Thoracic Computed Tomography Scans: Correlation of Radiomics-based Features With Radiation Therapy Dose and Radiation Pneumonitis Development

Abstract: Purpose To assess the relationship between radiation dose and change in a set of mathematical intensity- and texture-based features and to determine the ability of texture analysis to identify patients who develop radiation pneumonitis (RP). Methods and Materials A total of 106 patients who received radiation therapy (RT) for esophageal cancer were retrospectively identified under institutional review board approval. For each patient, diagnostic computed tomography (CT) scans were acquired before (0–168 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 36 publications
3
162
1
Order By: Relevance
“…Radiation pneumonitis is one of the drawbacks of lung irradiation, and it was investigated by Cunliffe et al 100 on patients affected by oesophageal cancer, considering CT images acquired before and after RT. A relationship between dose and texture variations was observed, and in particular, these changes were significantly related to radiation pneumonitis development in 12 features, consisting of the first and second order, fractal and Law's filter parameters.…”
Section: Radiation-induced Effects On Normal Tissuesmentioning
confidence: 99%
“…Radiation pneumonitis is one of the drawbacks of lung irradiation, and it was investigated by Cunliffe et al 100 on patients affected by oesophageal cancer, considering CT images acquired before and after RT. A relationship between dose and texture variations was observed, and in particular, these changes were significantly related to radiation pneumonitis development in 12 features, consisting of the first and second order, fractal and Law's filter parameters.…”
Section: Radiation-induced Effects On Normal Tissuesmentioning
confidence: 99%
“…Data mining and machine learning techniques are then used to build models and capture valuable insights from those imaging features. In the context of tumor analysis, univariate or multivariate models using these features have typically been built to diagnose lesions, [13][14][15] identify secondary effects, 16 or predict outcome. 6,12 Recent publications have demonstrated that a wide variety of radiomics features may predict NSCLC patient outcomes when extracted from computed tomography (CT), 6,12,17 contrast-enhanced CT, 18,19 or positron emission tomography (PET) [20][21][22] images.…”
Section: Introductionmentioning
confidence: 99%
“…These quantitative data extend beyond what is visible to the human eye and can be powerfully correlated with patient outcomes (99,100). The use of radiomics for lung cancer is an active area of study (101)(102)(103). For example, Van Timmeren and colleagues have shown that radiomic features of CBCT images are associated with survival after RT in NSCLC (104).…”
Section: Imaging For Treatment Response Assessment After Completion Omentioning
confidence: 99%